In vitro Micropropagation of Plumbago indica L. Through Induction of Direct and Indirect Organogenesis (Plant Tissue Culture and Biotechnology, 2010)
Leaf and nodal segments of two months old field grown seedlings of Plumbago indica L. were cultured on agar solidified MS supplemented with different concentrations and combinations of NAA, IAA, 2,4-D and picloram, and BAP and Kn. The nodal segments produced either multiple shoot buds (MSBs) or callus of different nature depending on the combinations of plant growth regulators (PGRs). The callus of light green and nodular shape, on further subculture on wide range of PGRs supplemented media, differentiated into MSBs. These MSBs underwent rapid elongation on different PGRs supplemented media. The elongated shoot buds were rooted on transferring in rooting medium and were acclimated in field with 90% survivability. The leaf segments, however, produced only white and friable calluses failed to undergo any differentiation in some of the media combinations.  Key words: Callus induction, Organogenesis, Plumbago indica D.O.I. 10.3329/ptcb.v19i2.5434 Plant Tissue Cult. & Biotech. 19(2): 169-175, 2009 (December)